2022
DOI: 10.3390/microorganisms10050909
|View full text |Cite
|
Sign up to set email alerts
|

Loop-Mediated Isothermal Amplification of Trypanosoma cruzi DNA for Point-of-Care Follow-Up of Anti-Parasitic Treatment of Chagas Disease

Abstract: A loop-mediated isothermal amplification assay was evaluated as a surrogate marker of treatment failure in Chagas disease (CD). A convenience series of 18 acute or reactivated CD patients who received anti-parasitic treatment with benznidazole was selected—namely, nine orally infected patients: three people living with HIV and CD reactivation, five chronic CD recipients with reactivation after organ transplantation and one seronegative recipient of a kidney and liver transplant from a CD donor. Fifty-four arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…4 and 9 ; see also Table S1 in the supplemental material), Sat-TcLAMP allowed the monitoring of parasitemia levels like qPCR, and thus, they can be used interchangeably for the early detection of the risk of reactivation in chronic infection ( Fig. 9 ); similar findings were described previously by Muñoz-Calderón et al ( 40 ) but in qualitative terms.…”
Section: Discussionsupporting
confidence: 77%
“…4 and 9 ; see also Table S1 in the supplemental material), Sat-TcLAMP allowed the monitoring of parasitemia levels like qPCR, and thus, they can be used interchangeably for the early detection of the risk of reactivation in chronic infection ( Fig. 9 ); similar findings were described previously by Muñoz-Calderón et al ( 40 ) but in qualitative terms.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, it can be used as an alternative extraction method. A previous study also showed that magnetic-bead extracted DNA had high agreement with spin-column extracted DNA for downstream LAMP testing [ 12 ]. However, samples with low viral loads may cause a false negative result when used with RT-LAMP detection.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, it has been described it could be of major relevance for the detection of acute T . cruzi infections like those found upon congenital transmission of the parasite or during oral outbreaks [ 5 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several LAMP procedures have already been proposed for the detection of T. cruzi infections [5][6][7][8][9][10]. The most studied of all has been the prototype kit developed by Eiken Chemical Company (Tokyo, Japan) based on T. cruzi nuclear satellite DNA (satDNA) sequences and containing dried reagents on the inside of the microtube caps, which has proven as sensitive as realtime quantitative PCR (qPCR) in blood samples collected from patients with acute, congenital and Chagas disease reactivations, as well as in patients under treatment monitoring [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%